Beyond partition: gender, violence, and representation in postcolonial India - Misri, Deepti (Dissident feminisms, 2014)
Anatomy of a riot: vulnerable male bodies in Manto and other fictions -- The violence of memory: women's re-narrations of the partition -- Atrocious encounters: caste violence and state violence -- "Are you a man?": performing naked in India -- "This is not a performance!": public mourning and visual spectacle in Kashmir -- Epilogue: the violence of the oppressed